Buffer zone prediction for simulated earthquake-induced slope failures in Mesilou, Kundasang, Sabah, Malaysia - H F W S Erfen; Baba Musta (IOP Publishing Ltd, 2022)
The research area is located at Mesilou, Kundasang, Sabah at 1400 meters to 2000 meters from the sea level. It focuses on slopes of Pinousuk Gravel Unit, tilloid deposits from the glaciation of Mount Kinabalu during Late Pleistocene age. Four slopes were chosen for the estimation of ‘buffer zone’ of earthquake-induced slope failures. The simulation of the earthquake is conducted by using shaking table method and the earthquake event occurred in the research area on year 2018. The analysis shows the location of the buffer zones are within 1.5 meters to 13.5 meters from the toe of the slope, where the run-out distance is farther with the increment of shaking’s duration and slope height. Simulation analysis shows that all slopes have detrimental impact of the settlement area of Kg. Mesilou, Kundasang but only 60% to 87% of respondents are still staying in the area. However, 74% to 84% of respondents are willingly to relocate if given new disaster-free settlements.